Closed‐loop automated oxygen control in ventilated infants born at or near term: A crossover trial. (27th November 2022) - Kaltsogianni, Ourania; Dassios, Theodore; Lee, Rebecca; Harris, Christopher; Greenough, Anne
Abstract: Aim: To determine if the use of closed‐loop automated oxygen control (CLAC) reduced the incidence and duration of hypoxemic episodes (SpO2 < 92%) in ventilated infants born at or above 34 weeks of gestation. Methods: Infants were studied on two consecutive days for 6 h each day. They were randomised to receive standard care (manual oxygen control) or standard care with a CLAC system (automated oxygen control) first. Results: Sixteen infants with a median (IQR) gestational age of 37.4 (36.6–38.8) weeks were studied at a median (IQR) postmenstrual age of 38.8 (37.4–39.8) weeks. During the automated oxygen control period, infants spent less time in hypoxemia (SpO2 < 92%) ( p = 0.033), episodes of desaturation were shorter ( p = 0.001), the time spent within target SpO2 range (92%–96%) was increased ( p = 0.001), and the FiO2 delivery was lower ( p = 0.018). The time spent in hyperoxemia (SpO2 > 96%) was reduced during automated oxygen control ( p = 0.011), the episodes of hyperoxemia were of shorter duration ( p = 0.008) and fewer manual adjustments were made to the FiO2 ( p = 0.005). Conclusions: Closed‐loop automated oxygen control in ventilated infants born at or near term was associated with a reduction in the incidence and duration of hypoxemic episodes with more time spent in the target oxygen range.